Investigation nonlinear behavior of radon gas (222Rn) - Kamishliglu, Mirac; Kulahci, Fatih (IEEE Computer Society, 2014)
For chaotic structure showed dynamic system chaos analysis are used phase space reconstruction, correlation dimension and maximum Lyapunov exponent method and such methods. Chaotic time series analysis method is benefit signal processing method for determine of nonlinear behavior of dynamic system. In this study, the methods explained for the chaotic analysis of the time series, which is obtained based on the discrete or continuous measurements of a variable. In this work, for dynamic system analysis, a time series occurred with radon ( 222Rn gas) concentration. Chaotic structure determine, the monitoring trajectory that is a quantitative analysis method and the qualitative analysis methods were used such as the Lyapunov exponent, correlation dimension and power spectrum analysis. © 2014 IEEE.
Radon gazinin (222Rn) lineer olmayan davranişinin incelenmesi
2014 22nd Signal Processing and Communications Applications Conference, SIU 2014 -- 23 April 2014 through 25 April 2014 -- Trabzon -- 106053
Keywords: Lyapunov methods; Phase space methods; Signal processing; Spectrum analysis; Time series analysis; Chaotic time series analysis; Continuous measurements; Correlation dimensions; Lyapunov exponent; Maximum Lyapunov exponent; Nonlinear behavior; Phase space reconstruction; Qualitative analysis; Radon